2015
DOI: 10.1186/s11671-015-0750-5
|View full text |Cite
|
Sign up to set email alerts
|

Vanadia supported on nickel manganese oxide nanocatalysts for the catalytic oxidation of aromatic alcohols

Abstract: Vanadia nanoparticles supported on nickel manganese mixed oxides were synthesized by co-precipitation method. The catalytic properties of these materials were investigated for the oxidation of benzyl alcohol using molecular oxygen as oxidant. It was observed that the calcination temperature and the size of particles play an important role in the catalytic process. The catalyst was evaluated for its oxidation property against aliphatic and aromatic alcohols, which was found to display selectivity towards aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…We have earlier reported mixed metal oxides [19,44,53,54] and metal oxides doped with other transition metals nanoparticles as catalyst such as Ag NPs doped manganese dioxide [44]. With the continued interest in our studies to find new and improved catalysts we carried out a comparative study of ZrO x -MnCO 3 or ZrO x -Mn 2 O 3 for the oxidation of primary alcohols [66] and it was found that the ZrO x -MnCO 3 was an excellent catalyst for the oxidation of primary aromatic alcohols to corresponding aldehydes with molecular O 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have earlier reported mixed metal oxides [19,44,53,54] and metal oxides doped with other transition metals nanoparticles as catalyst such as Ag NPs doped manganese dioxide [44]. With the continued interest in our studies to find new and improved catalysts we carried out a comparative study of ZrO x -MnCO 3 or ZrO x -Mn 2 O 3 for the oxidation of primary alcohols [66] and it was found that the ZrO x -MnCO 3 was an excellent catalyst for the oxidation of primary aromatic alcohols to corresponding aldehydes with molecular O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a significant effort has been made in order to explore eco-friendly and low cost catalysts 2 Advances in Materials Science and Engineering such as nonnoble metals like copper [32][33][34], cobalt [35][36][37], nickel [38][39][40], iron [41,42], vanadium [43], silver [44], chromium [45,46], molybdenum [47,48], rhenium [49], and zinc [50][51][52] for aerobic oxidation of alcohols. In addition, it has been extensively reported that the catalytic activity of mixed metal oxide nanoparticles catalysts enhanced remarkably upon doping with other metals probably due to the extremely high surface area of metal nanoparticles [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our efforts on the use of different mixed metal oxide nanoparticles as an efficient catalyst for the selective oxidation of alcohols in presence of molecular O 2 [18,32,41,48,49], we demonstrate herein a facile and straightforward procedure for the preparation of ZnO x NPs doped manganese carbonates or oxides employed for oxidation of secondary alcohols with environmentally friendly oxidizing agent such molecular O 2 which produces water as the only by-product under base-free conditions. The reaction circumstances have been optimized with different weight percentages of ZnO x , reaction times, calcination temperatures, reaction temperatures, and catalyst amounts using oxidation of 1-phenylethanol into acetophenone as a reaction model.…”
Section: Introductionmentioning
confidence: 99%
“…The metal, metal oxide, and mixed metal oxide nanoparticles catalysts were also found to be highly effective for the catalytic oxidation of alcohols. In addition, it has been widely reported that the catalytic activity of mixed metal oxide nanoparticles catalysts was remarkably enhanced upon doping with other metals, maybe because the metal nanoparticles possess huge surface area [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…14,[17][18][19][20][21][22][23][24] However, despite the recent surge in such studies, a lot more needs to be done in order to fully exploit the potential of graphene-based materials in biological applications. [25][26][27] Among the various challenges, the biocompatibility and toxicity of graphenebased materials both at in vitro and in vivo levels is one of the major challenges. 17 Several factors define the toxicity of these materials one of them is the use of hazardous chemicals employed in the synthesis of graphene-based materials, which needs special attention 14 towards their removal procedures for post-synthesis purification, which is one of the most important factors to conclude the biocompatibility of these materials.…”
Section: Introductionmentioning
confidence: 99%